Biomaterials - Wong, Joyce Y; Bronzino, Joseph D. (CRC Press, 2007)
Metalic biomaterials - Ceramic biomaterials - Polymeric biomaterials - Biodegradable hydrogels: tailoring properties and function through chemistry and structure - Biodegradable polymeric biomaterials: and updated overview - Biologic biomaterials: tissue-derived biomaterials (collagen) - Soft tissue replacements - Hard tissue replacements - Controlling and assessing cell-biomaterial. Interactions at the micro and nanoscale: applications in tissue engineering.